Perceived Impact of Epilepsy and Its Treatment on Pediatric Patients and Their Families - Redab Al-Ghawanmeh; Ala’a F. Al-Shaikh; Salma Burayzat; Ruba M. Jaber; Mohammad Al-Tamimi; Osama Zidan; Samah Aburahmeh (Children)
Background: Epilepsy is the most common chronic neurological condition in children, with a prevalence of 0.3% in Jordan. It significantly impacts patients’ and their families’ lives, shaped by cultural and socioeconomic factors. This study assessed the perceived impact of epilepsy on children and their families in Jordan. Method: This was a hospital-based, cross-sectional study recruiting 184 children under 18 years with epilepsy using a custom-designed questionnaire. Results: Nearly half of the patients experienced epilepsy onset before age three, and seizures were controlled in 73%. Around 60% of parents were satisfied with their understanding of the disease. Male gender and older age at diagnosis were associated with greater perceived severity, while older age at diagnosis correlated with a negative impact on caregivers’ earning potential. Patients with more anti-epileptic drugs reported more social constraints and older children expressed concerns about medication and seizure-related injuries. Cultural factors, such as family size and history, were associated with higher caregiver burden, emphasizing the importance of culturally sensitive assessment tools. Conclusions: Effective seizure control and quality of life improvements should be priorities in managing epilepsy in children. Cultural factors are strongly linked to caregiver burden, emphasizing the need for culturally sensitive assessment tools for enhancing support and care outcomes across diverse populations.